Review: Towards truly stall-free pork production? - K.J. Plush; R.J. Hewitt; D.N. D'Souza; R.J. van Barneveld (Animal, 2023)
The individual housing of sows and boars within stalls is still frequent in commercial pork production, especially when the risk for impaired reproduction or welfare is high. Whilst many countries have either removed stall housing in gestation or are working towards this through the successful adoption of group housing, stalls are still used around weaning and mating and in farrowing crates for sows. In this review, we describe the stages in which stall use still occurs and why this is so, with the aim of determining whether stall-free pork production can realistically be achieved through successful industry adoption. Group housing during the period around weaning, oestrus and mating will present several issues such as sow aggression, riding and mounting. This will result in injuries and reduced reproductive performance for the animals, and an unsafe work environment for stock people if not adequately addressed. The second, most obvious stage of the reproductive cycle where stalls are used and removal would result in substantial detriment is in the farrowing crate, where associated high preweaning mortalities still plague both experimental and commercial outcomes. The use of temporary confinement has received renewed interest recently to reduce this mortality, but still involves the strategic use of a stall when piglets are at greatest risk of crushing. To transition towards complete removal of stalls around farrowing, we suggest that space allowance, in combination with animal and staff experience, are areas of opportunity. If the concerns identified during these two final reproductive stages can be addressed to limit poor animal welfare and productivity impacts, the use of stalls could be completely removed from pork production.